Penerapan Nilai-Nilai Religius dalam Kegiatan Ekstrakurikuler PASKIBRA di Madrasah Aliyah Negeri 2 Kota Banjarmasin: Penelitian - Ajrina, Syahida; Huda, Nuril (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the religious values ​​applied in PASKIBRA extracurricular activities at MAN 2 Banjarmasin as well as the supporting and inhibiting factors that accompany it. This study is included in the type of field research using a qualitative approach. The subjects of this study were supervising teachers, trainers, and grade XII students who actively participated in PASKIBRA extracurricular activities at MAN 2 Banjarmasin. Research data were obtained through observation, interviews, and documentation. The results of this study indicate that the religious values ​​applied in PASKIBRA extracurricular activities at MAN 2 Banjarmasin are divided into four forms of values, namely worship values, moral values, discipline values, and exemplary values. The supporting factors for the implementation of religious values ​​in the PASKIBRA extracurricular activities at MAN 2 Banjarmasin include students' self-awareness of religion, adequate school facilities and infrastructure, and support from the school. Meanwhile, the inhibiting factors for the implementation of religious values ​​in the PASKIBRA extracurricular activities at MAN 2 Banjarmasin include limited time for activities, lack of structured planning, and limited supervision from supervising teachers and trainers.